Vegan/vegetarian diet and human milk donation: An EMBA survey across European milk banks - Serena Gandino; Agnieszka Bzikowska‐Jura; Karolina Karcz; Tanya Cassidy; Aleksandra Wesolowska; Barbara Królak‐Olejnik; Daniel Klotz; Sertac Arslanoglu; Jean‐Charles Picaud; Clair‐Yves Boquien; Enrico Bertino; Guido E. Moro; et al. (Wiley, 2024)
Abstract The nutritional adequacy of human milk (HM) from vegan/vegetarian mothers has been a matter of debate, and a variety of recommendations regarding the eligibility of these mothers as human milk donors exists. According to the latest evidence, HM from vegans/vegetarians is similar in its composition to that from omnivores, however, some differences may be observed regarding vitamin B12 and omega‐3 fatty acids concentrations. Maternal supplementation of these compounds has been proven effective in increasing their HM concentration. With this survey, we aimed to explore the practices currently in use in European human milk banks (HMBs) regarding potential donors following vegan/vegetarian diets. The online survey was distributed to European HMBs between January and July 2022. A total of 188 HMBs were contacted, and 118 replied (response rate 63%). Vegan and vegetarian mothers were recommended supplements of vitamin B12 to be accepted as donors in 27% and 26% of HMBs, respectively. Additional omega‐3 fatty acid supplementation was required in 8% HMBs. In the remaining HMBs, these mothers were either systematically excluded or included regardless of supplementation. The dosage of the recommended supplements was extremely variable. Fifty‐one percent of HMBs were following recommendations to guide their practice, national or local recommendations mainly. Great variability in European HMBs practices towards potential donors following vegan/vegetarian diets exists. Some of these practices can result in loss of donors and/or in potential nutritional deficiencies. Standardised evidence‐based recommendations on this issue and their implementation in daily HMB practice are needed.